Fanatik Dan Taksub dalam Islam: Analisis Pandangan Al-Qaradawi - Hj Ab Majid, Mohamad Kamil (Jurnal Usuluddin, 2003)
Religious fanaticism is a phenomenon that has been practised in Muslim society since a long time ago. Religion is regarded as the main factor that causes the arising and flourishing of this practice in Muslim society. Hence, the method or approach to be adopted to overcome this phenomenon should be based on Islamic teaching. This article attempts to highlight al- Qaradawi's point of view on how to approach and overcome this phenomenon in Muslim society of today. His opinion will be referred and analysed. The writer also discusses the issue in the context of Malay society.